2005
DOI: 10.1111/j.1365-3083.2005.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Experimental Arthritis with M2000, a Novel Designed Non‐Steroidal Anti‐Inflammatory Drug

Abstract: The current study was planned to explore the therapeutic potency of M2000 (b-D-mannuronic acid), a novel designed non-steroidal anti-inflammatory drug (NSAID) in adjuvant-induced arthritis model. Arthritis was induced in Lewis rats by a single intradermal injection (0.1 ml) of heat-killed Mycobacterium tuberculosis (0.3 mg) in Freund's incomplete adjuvant into the right footpad. Fourteen days after injection of adjuvant, the contralateral left footpad volume was measured. The animals with paw volumes 0.37 ml g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Of course, while ankle swelling does not reflect the full complement of peripheral inflammatory processes, it underscores the potential independence of pain and swelling in peripheral inflammatory pain states. Indeed, while both swelling and hypersensitivity can be dose-dependently reduced with non-steroidal anti-inflammatory drugs (NSAIDs; [49; 91]), hypersensitivity can also be attenuated independently from swelling [14; 37; 125]. Therefore, while ankle swelling alone should not be considered to be a definitive measure of the state of peripheral inflammation, it suggests that the processes underlying ongoing swelling may be unaffected by voluntary exercise, in contrast to pain- and stress-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, while ankle swelling does not reflect the full complement of peripheral inflammatory processes, it underscores the potential independence of pain and swelling in peripheral inflammatory pain states. Indeed, while both swelling and hypersensitivity can be dose-dependently reduced with non-steroidal anti-inflammatory drugs (NSAIDs; [49; 91]), hypersensitivity can also be attenuated independently from swelling [14; 37; 125]. Therefore, while ankle swelling alone should not be considered to be a definitive measure of the state of peripheral inflammation, it suggests that the processes underlying ongoing swelling may be unaffected by voluntary exercise, in contrast to pain- and stress-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The behaviors used to determine hypersensitivity include unlearned behaviors such as flinching, vocalization, and grooming (D'Amour and Smith, 1941; Woolfe and MacDonald, 1944; Randall and Selitto, 1957) or segmental withdrawal reflexes in response to thermal or mechanical stimulation (Hargreaves et al , 1988; Chaplan et al , 1994). Using models of inflammation induced by either carrageenan or CFA, researchers have demonstrated that the NSAID, indomethacin, reduces paw swelling in a dose-dependent manner by at least 60% (1–9 mg/kg, ip; Winter et al , 1962; Winter et al , 1968; Mirshafiey et al , 2005) and attenuates hyperalgesia and allodynia (2–4 mg/kg, ip; Hargreaves et al , 1988; Tall et al , 2004; Zhang et al , 2004). Interestingly, these components of inflammation (edema and hypersensitivity) do not necessarily go hand in hand.…”
Section: Commentarymentioning
confidence: 99%
“…The β‐D mannuronic acid (BDM) extracted from alginic acid sodium salt is a novel antiinflammatory agent with no evidence of toxicity in our preclinical toxicology study . Our previous studies have shown therapeutic efficacy of BDM with the high tolerability in various animal models such as experimental autoimmune encephalomyelitis , adjuvant‐induced arthritis , nephrotic syndrome , and acute glomerulonephritis . Currently, we are analyzing the efficacy of BDM in clinical trials in patients with ankylosing spondylitis (IRCT: 2013062213739N1) and rheumatoid arthritis (IRCT: 2014011213739N2).…”
Section: Introductionmentioning
confidence: 99%